The load-velocity slope is an indicator of the active drag in all competitive swimming strokes - Gonjo, T.; Vitazka, M.; Ljødal, I.; Olstad, B. H. (Medicine & Science in Sports & Exercise, 2025)
Introduction Active drag in swimming is a critical variable that affects swimmers' performance, as well as the physiological load, but it is challenging for practitioners to assess this variable. This study aimed to assess if the load-velocity profiling method can be used as an indicator of active drag.